THE CHRISTIAN LEGACY OF NILAKKAL: A HISTORICAL INQUIRY INTO ITS EARLY COMMUNITY AND FOURTEENTH-CENTURY DIASPORA - Santhan, Sunitha (ShodhKosh: Journal of Visual and Performing Arts, 2023)
Christianity in Kerala can be traced back to the beginning of the Christian era. According to tradition, St. Thomas is believed to have arrived at Malayankara near Cranganore in 52 AD, where he preached the Gospel and established seven churches in Malabar. These churches were located in Cranganore, Quilon, Niranam, Nilakkal, Kokamangalam, Kottakavu–Parur, and Palayur. Among these early Christian centres, where the Apostle is said to have evangelized and founded Christian communities, Nilakkal stands out as the only site that remains uninhabited and desolate. Historical evidence suggests that thriving Christian and Hindu communities coexisted in Nilakkal until the mid-fourteenth century. Various traditions and accounts exist regarding the mass exodus of the Christian community from Nilakkal. This study examines the presence of the Christian community in Nilakkal and explores the factors contributing to their large-scale migration to other parts of Kerala by the end of the fourteenth century.